ANALISIS TINGKAT VALIDITAS MEDIA BUKU BERGAMBAR “CALIS” BERBASIS KARAKTER UNTUK MENINGKATKAN KEMAMPUAN BACA-TULIS SISWA ADHD DI SDN SIDOREJO II TUBAN - agustin, ina; Mubarokah, Shobihatul (JPB - Jurnal Pendidikan Biologi, 2023)
Children with ADHD are children with special needs who need special services and attention, especially in formal education. Children with ADHD or often called hyperactive experience difficulties in learning because of difficulty concentrating. The learning difficulties referred to are difficulties in reading and writing at the beginning. To overcome the difficulties he faces, it is necessary to use interesting media so that he can focus his concentration and make him more enthusiastic about learning so that he can improve his reading and writing skills. Researchers used the picture book "CALIS" as an appropriate medium to help the learning process of students with ADHD. The purpose of this study was to determine the validity level of the character-based "CALIS" picture book media to improve the literacy skills of ADHD students at SDN Sidorejo II Tuban. This study uses a research and development approach (Research and Development). The development model used by researchers is the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data analysis technique used is descriptive qualitative and quantitative data analysis. Quantitative data uses material, media and language expert validation sheets. The final conclusion of the validity results is as follows: (1) the level of validity of the material expert is stated to be very valid with a result of 90%. (2) the validity level of the media expert is stated to be valid with a score of 80%. (3) the validity level of the linguist is stated to be very valid with a score of 93.33%. The results of this validation show that the developed "CALIS" picture book media is declared valid and ready to be used as a learning medium for children with ADHD class II at SDN Sidorejo II Tuban.